The Use and Abuse of Perichoresis in Recent Theology - Otto, Randall E. (Scottish journal of theology, 2001)
Perichoresis (perichoresis, circumincessio) is a theological term which describes the ‘necessary being-in-one-another or circumincession of the three divine Persons of the Trinity because of the single divine essence, the eternal procession of the Son from the Father and of the Spirit from the Father and (through) the Son, and the fact that the three Persons are distinguished solely by the relations of opposition between them.’ This term was popularized in the eighth century by John of Damascus who, in his De fide orthodoxa, said the three Persons of the Trinity ‘are made one not so as to commingle, but so as to cleave to each other, and they have their being in each other [kai ten en allelais perichoresin] without any coalescence or commingling.’ This important theological term, which Karl Barth rightly regarded 'as the one important form of the dialectic required to complete the concept of ‘three-in-oneness’ ‘from the side of the unity of the divine essence’ and ‘from the side of the original relations,’ has suffered in some recent theology from its appropriation to describe relationality apart from mutually shared being. For example, in his influential social doctrine of the Trinity, Jürgen Moltmann emphasizes the ‘relational, perichoretically consummated life processes’ of the three Persons who ‘cannot and must not be reduced to three modes of being of one and the same divine subject,’ whose unity ‘cannot and must not be seen in a general concept of divine substance.’